Women are started on a lower daily dose of metoprolol than men irrespective of dose recommendations: A potential source of confounding by contraindication in pharmacoepidemiology. Issue 7 (29th March 2021) - Hendriksen, Linda C.; Verhamme, Katia M. C.; Van der Linden, Paul D.; Stricker, Bruno H.; Visser, Loes E.
Abstract: Purpose: Current guidelines have no sex‐specific dosage advice for metoprolol. To evaluate whether women and men are prescribed the same dose a cohort analysis was performed in the population‐based Rotterdam Study (RS). Results were replicated in the Integrated Primary Care Information (IPCI) database of automated general practice data. Methods: The mean daily starting doses of metoprolol in both sexes were compared with independent‐samples t‐tests and a linear regression analysis was used to adjust in the RS for co‐variables, notably, cardiovascular comorbidity, migraine, age, SBP, DBP, BMI, socioeconomic status, use of other antihypertensive drugs, smoking, and alcohol. In the IPCI‐database, adjustment was for age only. Results: The mean daily starting dose was statistically significantly lower in women than in men in both the RS and IPCI database, with a mean difference of 4.8 mg (95%CI −7.8, −1.8) and 4.6 mg (95%CI −5.3, ‐4.0), respectively. Statistical significance remained after adjustment in both databases. Conclusions: Women received lower starting doses of metoprolol than men in two independent data collections despite non‐sex specific cardiovascular guideline recommendations. This example of real‐life pharmacotherapy can lead to a form of confounding by contraindication in pharmacoepidemiology.